2017
DOI: 10.1177/2048872617722486
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of ST-segment change after return of spontaneous cardiac arrest and emergent coronary angiography in patients with out-of-hospital cardiac arrest: Diagnostic and therapeutic importance of vasospastic angina

Abstract: An acute culprit lesion may be the cause of OHCA even in the absence of STE. In survivors of OHCA with normal coronary arteries, spasm provocation testing should be performed to detect VSA as a cause of the arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Imaging using a 64-slice coronary computed tomography angiogram and coronary angiography are useful for detecting ARCAPA. Emergency coronary angiography may identify acute culprit lesions of acute coronary syndrome in patients with out-of-hospital cardiac arrest, regardless of any ST segment changes ( 6 ). We therefore performed emergency coronary angiography as soon as the patient's vital signs stabilized and found that the left main coronary artery arose from the appropriate sinus without aneurysm or stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging using a 64-slice coronary computed tomography angiogram and coronary angiography are useful for detecting ARCAPA. Emergency coronary angiography may identify acute culprit lesions of acute coronary syndrome in patients with out-of-hospital cardiac arrest, regardless of any ST segment changes ( 6 ). We therefore performed emergency coronary angiography as soon as the patient's vital signs stabilized and found that the left main coronary artery arose from the appropriate sinus without aneurysm or stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, coronary spasms occasionally play an important role in ventricular arrhythmia. Recent studies have demonstrated that VSA accounts for 8%–11% of out-of-hospital cardiac arrests [ 25 , 26 ], and a Japanese multicenter registry showed that out-of-hospital cardiac arrest is the strongest predictor of future major adverse events in patients with VSA [ 4 ]. This study found that VSA accounted for 18% of SCA etiologies in a secondary prophylactic population.…”
Section: Discussionmentioning
confidence: 99%
“…For patients in whom a cardiac cause is suspected and post-ROSC ECG shows ST-segment elevation (as it did in our patient), studies have shown that early invasive management with CC is needed with possible percutaneous coronary intervention, thus making it an integral part of the post-CA care guidelines (1) . A recent study demonstrated that a culprit coronary lesion could be found in up to 81% of patients with ST-segment elevation on post-ROSC ECG (3) . This is in contrast to non-ST-segment elevation MI patients in post-CA with no difference in survival with immediate versus delayed angiography (4) .…”
Section: Discussionmentioning
confidence: 99%